Cumulative Cognition: Strengthening Learning with Progressive Content Delivery - Carley Yawn; Logan Van Ravenswaay; Krista Marcello; Sarah Nisly (Journal of CME)
Cognitive research consistently demonstrates that spaced repetition enhances memory consolidation and retrieval by reinforcing learned material over time. This study applies the Precede–Proceed Model of Learning framework to examine how predisposing, enabling, and reinforcing educational strategies support sustained knowledge retention among healthcare professionals. The analysis focused on three accredited continuing professional development (CPD) programs conducted between 2022 and 2024. Participants engaged in educational activities that included baseline pre-test and post-activity post-test assessments, with exposure categorized based on prior interaction with related content. Learners were stratified into groups by timing and frequency of exposure to the material. The primary outcome measured was improvement in test performance across sequential learning engagements. Results indicated that learners who accessed educational content prior to the activity demonstrated a significantly higher mean pre-test score of 31% (n = 443) compared to 27% (n = 1,416) among those who viewed it afterward (p = 0.041). Furthermore, repeat learners, regardless of content timing, achieved greater knowledge gains, improving by 34% (p < 0.001), in contrast to a 26% improvement among first-time learners (p < 0.001). These findings highlight the additive value of progressive and repeated exposure in CPD programs. By analysing longitudinal engagement patterns, this study reinforces the importance of strategically structured educational design to foster enduring clinical competence.